(untitled) (Research, Society and Development, 2021)
The human papillomavirus (HPV) is a sexually transmitted infection (STI), with the ability to infect epithelial cells, and can be asymptomatic or generate lesions on the skin and mucosa, such as simple warts, genital warts and condylomas, and neoplasms such as oropharyngeal cancer. The overall objective of this study was to evaluate the knowledge of young high school students from a public school in the city of Uberaba-MG about the relationship between HPV infection and the development of oropharyngeal cancer, and to intervene with a lecture about oropharyngeal cancer caused by HPV for further evaluation of the knowledge acquired. A before and after study was done with 59 high school students from a public school, using sociodemographic questionnaires and questionnaires about HPV. The level of knowledge of the students was evaluated with the first round of questionnaires. Then, a lecture was held reporting the main characteristics and importance of HPV prevention and its relationship with oropharyngeal cancer. Then, the second stage of questionnaires, reassessing the learning obtained after the lecture and the understanding of the subject. It was evidenced limited knowledge by the population about the relationship between HPV and the emergence of neoplasms. It was possible to observe an important increase in knowledge about this sexually transmitted infection, including its signs and symptoms, forms of contamination and methods of prophylaxis, besides its relationship with oropharyngeal cancer, when a lecture/lecture was given. The results about this study on the knowledge of high school students about the HPV infection and the development of oropharyngeal cancer, shows the lack of knowledge of individuals from a public school in Uberaba on the subject, noticeable by the data collected after applying a form to these young people.